Helicoverpa zea (Lepidoptera: Noctuidae) and Spodoptera frugiperda (Lepidoptera: Noctuidae) Responses to Sorghum bicolor (Poales: Poaceae) Tissues From Lowered Lignin Lines. Issue 1 (17th January 2015) - Dowd, Patrick F.; Sattler, Scott E.
Abstract : The presence of lignin within biomass impedes the production of liquid fuels. Plants with altered lignin content and composition are more amenable to lignocellulosic conversion to ethanol and other biofuels but may be more susceptible to insect damage where lignin is an important resistance factor. However, reduced lignin lines of switchgrasses still retained insect resistance in prior studies. Therefore, we hypothesized that sorghum lines with lowered lignin content will also retain insect resistance. Sorghum excised leaves and stalk pith Sorghum bicolor (L.) Moench (Poales: Poaceae) from near isogenic brown midrib ( bmr ) 6 and 12 mutants lines, which have lowered lignin content and increased lignocellulosic ethanol conversion efficiency, were examined for insect resistance relative to wild-type (normal BTx623). Greenhouse and growth chamber grown plant tissues were fed to first-instar larvae of corn earworms, Helicoverpa zea (Boddie) and fall armyworms Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), two sorghum major pests. Younger bmr leaves had significantly greater feeding damage in some assays than wild-type leaves, but older bmr6 leaves generally had significantly less damage than wild-type leaves. Caterpillars feeding on the bmr6 leaves often weighed significantly less than those feeding on wild-type leaves, especially in the S. frugiperda assays. Larvae fed the pith from bmr stalks had significantly higher mortality compared with those larvae fed on wild-type pith, which suggested that bmr pith was more toxic. Thus, reducing lignin content or changing subunit composition of bioenergy grasses does not necessarily increase their susceptibility to insects and may result in increased resistance, which would contribute to sustainable production.